Effectiveness of an IMB-Based Stunting Prevention Model Among Adolescents: A Quasi-Experimental Study - Permatasari, Dian; Indriyani, Ratna; Hannan, Mujib; Suprayitno, Emdat; Puspitasari, Dian Ika (Lembaga Chakra Brahmanda Lentera (Chakra Brahmanda Lentera Institute) [CANDLE], 2025)
Background: Stunting remains a significant public health issue in Indonesia. Conventional interventions often focus on pregnancy and early childhood, showing limited sustainability. Adolescents, as prospective parents, represent a strategic target for sustainable prevention, yet evidence on effective behavior change models for this group remains limited. Methods: This quasi-experimental study adhered to the TREND guideline. Female adolescents (N=120) aged 15-20 years from schools and Islamic boarding schools in Sumenep were randomly assigned to an intervention group (n=60) that received a structured IMB-based program or a control group (n=60) that received standard education. The intervention comprised sessions on information, motivation, and behavioral skills. Dependent variables were knowledge, motivation, and behavior, measured via validated questionnaires. Data were analyzed using Mann-Whitney U tests with significance at p < 0.05 Result: The intervention group showed significant improvements in knowledge (85% good post-test vs. 13.3% pre-test, p < 0.001), motivation (75% high post-test vs. 11.7% pre-test, p < 0.001), and behavior (90% good post-test vs. 11.6% pre-test, p < 0.001). The control group showed no significant changes. Conclusion: The IMB model effectively enhances stunting prevention knowledge, motivation, and behavior among adolescents. It is recommended for integration into adolescent health programs in similar LMIC settings.